Предмет: Алгебра,
автор: yatiya
Упростить выражение ................
Приложения:
![](https://files.topotvet.com/i/0e3/0e371d5b4c627b5f23003900e7b3f10b.png)
Ответы
Автор ответа:
0
1) (а^ 1/3 - a^ 7/3)/(a^ 1/3 - a^ 4/3) =
= (a^ 1/3 · (1 - a²)) : (a^ 1/3 · (1 - a)) =
= (1 + a)
2) (а^ -1/3 - a^ 5/3)/(a^ 2/3 + a^ -1/3) =
= (a^ -1/3 · (1 - a²)) : (a^ -1/3 · (1 + a)) =
= (1 - a)
3) 1 + a - (1 - a) = 2a
Ответ: 2а
= (a^ 1/3 · (1 - a²)) : (a^ 1/3 · (1 - a)) =
= (1 + a)
2) (а^ -1/3 - a^ 5/3)/(a^ 2/3 + a^ -1/3) =
= (a^ -1/3 · (1 - a²)) : (a^ -1/3 · (1 + a)) =
= (1 - a)
3) 1 + a - (1 - a) = 2a
Ответ: 2а
Похожие вопросы
Предмет: Математика,
автор: Nihis
Предмет: Русский язык,
автор: ramazanisembaev6
Предмет: Русский язык,
автор: 197007fijn
Предмет: Литература,
автор: 1211198412
Предмет: Математика,
автор: lina281